2019
DOI: 10.1097/md.0000000000016393
|View full text |Cite
|
Sign up to set email alerts
|

Fenestration deformity of the basilar artery trunk with an aneurysm

Abstract: Rationale: Fenestration of the basilar artery is most common in the proximal portion near the vertebrobasilar artery junction. Conversely, fenestration of the middle and distal portions of the basilar artery is not common, and fenestration of the basilar artery with an aneurysm is even less common. Patient concerns: This study reports the case of a 37-year-old woman with basilar artery fenestration malformation and an aneurysm at the mid-distal junction; her symptoms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…The histopathological findings in fenestrations are imperfect medial membrane at both edges of the fenestration, elastin defect, and thinning of the subendothelial layer at the proximal end, resulting in a weakened vessel wall. These intrinsic defects coupled with altered hemodynamics (high shear stress and high-speed turbulence) contribute to aneurysm formation and rupture [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The histopathological findings in fenestrations are imperfect medial membrane at both edges of the fenestration, elastin defect, and thinning of the subendothelial layer at the proximal end, resulting in a weakened vessel wall. These intrinsic defects coupled with altered hemodynamics (high shear stress and high-speed turbulence) contribute to aneurysm formation and rupture [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fenestration of the middle and distal segments is a rare occurrence. Currently, the literature regarding BAF is sparse and is confined mainly to case reports and series [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In cases involving a vascular structure such as that in the present case, the herein-described technique may be considered an option for treatment. Zhang et al 17 reported that occlusion of the minor limb is relatively safe when no perforating arteries are present. However, Im et al 6 reported a case of small perforators originating from both the major and minor limbs of an upper BA fenestration.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]7,8 An aneurysm arising from an upper BA fenestration is extremely rare. We identified only 15 cases in the literature, 3,9-16 including 1 case in the middle-upper part 17 and our case (Table 1). Very few unruptured aneurysms have been reported, and ours is the fifth such case.…”
Section: Observationsmentioning
confidence: 99%
“…The shape of cerebrovascular fenestration malformations can be divided into silk-like shape, convex-lens-like shape, duplication shape and irregular shape [ 2 ]. Studies have reported that cerebrovascular fenestration deformity may be related to aneurysms, moyamoya disease, transient ischemic attack, cerebral infarction and other diseases [ 3 , 4 , 5 ]. For young patients with acute cerebral infarction, we must do a good job in differential diagnosis with other etiologies.…”
Section: Introductionmentioning
confidence: 99%